2012
DOI: 10.1183/09031936.00225711
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific embryonic antigen-4is expressed in basaloid lung cancer and associated with poor prognosis

Abstract: Basaloid carcinoma represents a rare variant of nonsmall cell lung cancer (NSCLC), which has shown a poor prognosis in a number of studies. Although it is considered to derive from a pluri-or multipotent pulmonary stem cells, little is known about the expression and clinical significance of stem cell antigens in this variant.Stage-specific embryonic antigen-4 (SSEA-4) was analysed by immunohistochemistry in 38 patients with resected early-stage basaloid NSCLC who had a median follow-up of 72.9 months. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…It is well known that cancer cells recapitulate traits from normal early embryonic cells. In this connection, SSEA‐4 expression was found in teratocarcinomas, renal cell carcinoma, glioblastoma, breast cancer, basaloid lung cancer, epithelial ovarian carcinoma, embryonal carcinoma of the ovaries, pheochromocytoma, prostate cancer and oral cancer . Furthermore, SSEA‐4 is expressed in multiple cancer cell lines, including brain, lung, breast, mouth, esophagus, stomach, liver, kidney, cervix, ovarian, prostate, colon and pancreatic cancers .…”
Section: Introductionmentioning
confidence: 91%
“…It is well known that cancer cells recapitulate traits from normal early embryonic cells. In this connection, SSEA‐4 expression was found in teratocarcinomas, renal cell carcinoma, glioblastoma, breast cancer, basaloid lung cancer, epithelial ovarian carcinoma, embryonal carcinoma of the ovaries, pheochromocytoma, prostate cancer and oral cancer . Furthermore, SSEA‐4 is expressed in multiple cancer cell lines, including brain, lung, breast, mouth, esophagus, stomach, liver, kidney, cervix, ovarian, prostate, colon and pancreatic cancers .…”
Section: Introductionmentioning
confidence: 91%
“…In the last few years, SSEA-4 expression has been reported on breast cancer cells and breast cancer stem cells (25), basaloid lung cancer (30), epithelial ovarian carcinoma (31), and oral cancer (32). The relationship between the level of SSEA-4 expression and tumor malignancy differs in various types of cancers: The expression of SSEA-4 in basaloid lung cancer is associated with poor prognosis (30), whereas a reduction of SSEA-4 correlates with more advanced tumor stage and tumor cell differentiation in ovarian cancer (31). Here, we examined the expression of SSEA-4 in GBM and found that SSEA-4 is expressed not only in GBM/grade IV astrocytoma but also in ∼55% of grade I, ∼55% of grade II, and ∼60% of grade III astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance not only is a characteristic of malignancies but also considered as one of the features being utilized to define cancer stem‐like cells ever since the CSC hypothesis became a popular explanation to those cases of cancer that recur after medical treatment . In colorectal cancer and leukaemia, conventional chemotherapeutic drug 5‐fluorouracil enriches CSC population .…”
Section: Discussionmentioning
confidence: 99%